Fluorescence properties of a potential antitumoral benzothieno[3,2-b]pyrrole in solution and lipid membranes - Castanheira, Elisabete M. S. (2009)
Fluorescence properties of the antitumoral methyl 3-(benzo[b]thien-2-yl)-benzothieno[3,2-b]pyrrole-2-carboxylate (BTP) were studied in solution and in lipid bilayers of dipalmitoyl phosphatidylcholine (DPPC), dioleoyl phosphatidylethanolamine (DOPE) and egg yolk phosphatidylcholine (Egg-PC). BTP presents good fluorescence quantum yields in all solvents studied (0.20 ≤ ΦF ≤ 0.32) and a bathochromic shift in polar solvents. The results indicate an ICT character of the excited state, with an estimated dipole moment of μe = 7.38 D. Fluorescence (steady-state) anisotropy measurements of BTP incorporated in lipid membranes of DPPC, DOPE and Egg-PC indicate that this compound is deeply located in the lipid bilayer, feeling the difference between the rigid gel phase and fluid phases. BTP inhibits the growth of three human tumour cell lines, MCF-7 (breast adenocarcinoma), SF-268 (glioma) and NCI-H460 (non-small cell lung cancer), being significantly more potent against the NCI-H460 tumour cells.